A comparison study on the growth pattern of traffic oscillations in car-following experiments. Issue 1 (31st December 2023) - Zheng, Shi-Teng; Jiang, Rui; Tian, Junfang; Li, Xiaopeng; Jia, Bin; Gao, Ziyou; Yu, Shaowei
Abstract : A recent car-following experiment (Experiment-I) showed that the speed standard deviation grows in a concave way along a platoon of vehicles following one another. This paper investigates the growth pattern of traffic oscillations in a platoon in another car-following experiment (Experiment-II) and compares it with that in Experiment-I. It is shown that the speed standard deviation also exhibits concave growth characteristics in Experiment-II. The hypothesis test show that there is no significant difference in growth pattern of speed standard deviation between the two experiments. However, since drivers are asked to follow closely in Experiment-II, the acceleration standard deviations, the driver sensitivities, and the strength of stochastic factors are larger than the ones in Experiment-I. Furthermore, a new comparison experiment is performed which indicates that traffic oscillation growth in the platoon in the set of experiments on a circular track is likely to be equivalent to that on a straight track.